2012
DOI: 10.1111/pbi.12024
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating cellulose biosynthesis by expression of mutant Arabidopsis proM24::CESA3ixr1‐2 gene in transgenic tobacco

Abstract: Summary Manipulation of the cellulose biosynthetic machinery in plants has the potential to provide insight into plant growth, morphogenesis and to create modified cellulose for anthropogenic use. Evidence exists that cellulose microfibril structure and its recalcitrance to enzymatic digestion can ameliorated via mis‐sense mutation in the primary cell wall–specific gene AtCELLULOSE SYNTHASE (CESA)3. This mis‐sense mutation has been identified based on conferring drug resistance to the cellulose inhibitory herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Both mutations cause a decrease in cellulose crystallinity. Expression of a defective cellulose synthase CesA3 (eli1) is correlated with a lignin enrichment in H units [65] suggesting that over-expression of a defective cellulose synthase could be used to enhance the ratio between crystalline and amorphous cellulose as shown in tobacco [66 ] and boost the accumulation of H units to reduce lignin DP and recalcitrance.…”
Section: Increasing Wall Sugarsmentioning
confidence: 98%
“…Both mutations cause a decrease in cellulose crystallinity. Expression of a defective cellulose synthase CesA3 (eli1) is correlated with a lignin enrichment in H units [65] suggesting that over-expression of a defective cellulose synthase could be used to enhance the ratio between crystalline and amorphous cellulose as shown in tobacco [66 ] and boost the accumulation of H units to reduce lignin DP and recalcitrance.…”
Section: Increasing Wall Sugarsmentioning
confidence: 98%
“…DaMV contains a circular double-stranded DNA of approximately 8 kb, with four single-stranded interruptions (Richins and Shepherd 1983) and six genes (http://dahlia.wsu.edu/ vectorcontrol/whatsknowndmv.htm). Generally, two major transcriptional promoters are present in most of the caulimovirus genome; these two promoters are the fulllength transcript (Flt) and the subgenomic transcript (Sgt) promoters, which have been studied previously in cauliflower mosaic virus (CaMV), figwort mosaic virus (FMV), peanut chlorotic streak virus (PClSV), strawberry vein mosaic virus (SVMV), and mirabilis mosaic virus (MMV) (Bhattacharyya et al 2002;Maiti et al 1997;Maiti and Shepherd 1998;Odell et al 1981;Pattanaik et al 2004;Dey and Maiti 1999;Sahoo et al 2009Sahoo et al , 2013Kroumova et al 2013;. Similarly, our recent data (Sahoo et al 2014b) also revealed that the DaMV genome possesses the Flt and Sgt promoters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Penning et al have recently shown that quantitative trait loci (QTLs) for lignin abundance are independent of those for saccharification in a maize recombinant inbred population (14). In particular, altering cellulose production, deposition, or crystallinity can affect saccharification (15)(16)(17) because cellulose typically constitutes around one third of the total mass of plants and the insoluble crystalline cellulose fibers are hard to digest (18). Alterations in matrix polysaccharide content and composition can also affect saccharification (19,20) by changing the extractability and/or architecture of the cell wall.…”
mentioning
confidence: 99%